The Effect of Trade Openness on Economic Growth in Jordan: An Analytical Investigation (1992-2015) - Obeid, Rami; Awad, Bassam (International Journal of Economics and Financial Issues, 2018)
This study aims at measuring the effect of trade openness and financial development on economic growth in Jordan based on quarterly data for the period (1992-2015). Two forms were used for measuring the effect of trade openness on economic growth using the Autoregressive Distributed lag model (ARDL). The results showed that there exists a long-term positive effect of trade openness (measured by the ratio of sum of exports and imports to GDP) and financial development (represented by the ratio of both credit extended to the private sector and broad money supply to GDP) on economic growth in Jordan. For the short-term impact, the effect of trade openness and financial development on economic growth was not statistically significant. Keywords: Trade openness, economic growth, Jordan JEL Classifications: F17, F43, O47